Food value chains for nutrition - Allen, Summer L.; Maestre, Mar; Gelli, Aulo (International Food Policy Research Institute, 2019)
Despite global goals to decrease malnutrition, there remain many challenges in providing access to a nutritious diet for all. Food value chains for nutrition have been the focus of a number of reviews but evidence of their impacts remains limited. Using a systems perspective to look at markets and the role of the private sector in nutrition includes not only the complex relations between multiple actors and trade-offs between often competing objectives, but also the supporting environment in terms of infrastructure (e.g. roads, energy) and the guiding laws and social norms.